2022
DOI: 10.14201/scero2022537594
|View full text |Cite
|
Sign up to set email alerts
|

La provisión de apoyos fuera del aula como medida de atención a la diversidad y sus efectos en la inclusión educativa

Abstract: Este estudio analiza el impacto del apoyo fuera del aula como medida de atención a la diversidad en el alumnado de primaria, además de las nominaciones positivas y negativas que emiten y reciben, así como sus perfiles sociométricos. La muestra representa a 20 colegios ordinarios de la región de Extremadura (España). Participaron 881 alumnos (de 6 a 12 años) pertenecientes a 43 aulas de primaria, de primero a sexto curso; de estos, 98 alumnos (11,12 %) presentaban necesidades específicas de apoyo educativo. Com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 13 publications
0
3
0
1
Order By: Relevance
“…Of these children, 32.6% were rejected, a figure that more than doubles the rejection rate reported in the literature on non-needs students, and that concurs with other authors [14]; special needs students suffer greater rejection. It would be interesting to conduct longitudi-nal studies in order to determine whether this figure increases as children advance through the education system [18].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Of these children, 32.6% were rejected, a figure that more than doubles the rejection rate reported in the literature on non-needs students, and that concurs with other authors [14]; special needs students suffer greater rejection. It would be interesting to conduct longitudi-nal studies in order to determine whether this figure increases as children advance through the education system [18].…”
Section: Discussionmentioning
confidence: 99%
“…It has also been found that this phenomenon mainly affects boys [16], with the latter being more likely to be victims of bullying than girls [17], who are generally more preferred in the classroom [15,16]. It is also important to mention that students with specific educational support needs (SEN) are more prone to suffer rejection [14], and that this increases as they progress through the education system [18].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Esta carencia tiene un impacto negativo en su desarrollo académico, ya que la lectura se considera una herramienta fundamental para abordar cualquier tipo de información en las diferentes asignaturas del plan de estudios de formación profesional. Complementando, Rodríguez et al, (2023) afirman que en variados momentos los educadores se ponen en discordia al reto de que los discentes no ejecutan las lecturas proporcionadas antes de arribar a clases, bajando el ritmo de interacción con el docente y por ende, del aprendizaje.…”
Section: Introductionunclassified